The Effect of Relaxation Therapy, Benson and Murotal Al-Qur'an Surah Ar Rahman, on the Sleep Quality of Hypertensive Patients in The Kaliwungu Kudus Health Center Area - Lu'lu'atul Isna Faridah; Sukarmin Sukarmin; Sri Siska Mardiana (Advances in Healthcare Research, 2026)
Purpose: This study aims to analyze the effect of combining Benson relaxation therapy with the recitation of Surah Ar-Rahman of the Qur'an on sleep quality in hypertensive patients.   Research Method: This study uses a quasi-experimental design with a control group approach. A total of 40 respondents were divided into two groups: the intervention group, which received a combination of Benson relaxation therapy and Surah Ar-Rahman murottal, and the control group, which received no treatment. Respondents' sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI) instrument. Results and Discussion: The results showed a significant improvement in sleep quality in the intervention group after therapy, while the control group showed no significant change. Statistical analysis yielded a p-value of 0.000 (p < 0.05), indicating that the combination of Benson's relaxation therapy and recitation of Surah Ar-Rahman from the Qur'an significantly improved sleep quality in hypertensive patients. These findings suggest that the combination of therapies can serve as a safe, easy-to-apply, non-pharmacological intervention to improve sleep quality in hypertensive patients. Implications: The practical implication of these findings is that healthcare professionals can incorporate Benson therapy and the recitation of Surah Ar-Rahman as a non-pharmacological intervention in the management of hypertension. This method is easy to implement both in healthcare facilities and independently at home, thereby helping to improve sleep quality, reduce stress, and support patients’ blood pressure control.